EBV-Infection in Cardiac and Non-Cardiac Gastric Adenocarcinomas is Associated with Promoter Methylation of p16, p14 and APC, but not hMLH1. (2010) - Geddert, Helene; Hausen, Axel zur; Gabbert, Helmut E.; Sarbia, Mario
Abstract : Background : Epstein–Barr virus (EBV)-associated gastric carcinomas (GC) constitute a distinct clinicopathological entity of gastric cancer. In order to determine underlying distinct aberrant promoter methylation we tested cardiac and non-cardiac GC with regard to the presence of EBV. Methods : One hundred GC were tested by RNA-in situ hybridization for the presence of EBV by EBV-encoded small RNA (EBER). Aberrant promoter methylation was investigated by methylation-specific real-time PCR for p16, p14, APC and hMLH1. P16 protein expression was assessed by immunohistochemistry. Results : In our selected study cohort, EBER-transcripts were detected in 19.6% (18/92) of GC. EBV-positive GC revealed significantly more often gene hypermethylation of p16, p14 and APC (p < 0.0001, p < 0.0001 and p = 0.02, respectively) than EBV-negative GC. The majority of GC with p16 hypermethylation showed a p16 protein loss (22/28). In contrast, no correlation between the presence of EBV and hMLH1 hypermethylation was found (p = 0.7). EBV-positive GC showed a trend towards non-cardiac location (p = 0.06) and lower stages (I/II) according to the WHO (p = 0.05). Conclusion : Hypermethylation of tumor suppressor genes is significantly more frequent in EBV-associated GC compared to EBV-negative GC. Our data add new insights to the role of EBV in gastric carcinogenesis and underline that EBV-associated GC comprise a distinct molecular-pathologic as well as a distinct clinicopathological entity of GC.